Legal Protection for Consumers Against the Circulation of Hazardous Cosmetic Products: Between Regulation and Law Enforcement in Indonesia - Savina; Suwarno Abadi (International Journal of Science and Society, 2026)
The increasing circulation of cosmetic products containing hazardous substances in Indonesia has raised significant concerns regarding consumer safety and legal protection. This study aims to analyze consumer legal protection against the misuse of hazardous substances in cosmetic products through a comprehensive literature review approach. This study also examines regulatory challenges and law enforcement obstacles related to the supervision of hazardous cosmetic products in Indonesia. The research employs a qualitative method with a literature review approach through the collection and analysis of scientific journal articles, legal documents, government regulations, and official reports concerning cosmetic supervision and consumer protection. The findings indicate that hazardous substances such as mercury, hydroquinone, and other illegal chemical compounds are still frequently found in illicit cosmetic products distributed through both offline channels and digital marketplaces. This study reveals that weak regulatory oversight, limited institutional coordination, and the rapid growth of online commerce have complicated the effectiveness of cosmetic control mechanisms. Law enforcement efforts continue to face various obstacles, including difficulties in investigation processes, limited sanctions, and low legal awareness among business actors. The analysis also shows that existing consumer protection regulations have not fully addressed the dynamic challenges in the distribution of hazardous cosmetics in Indonesia. Strengthening the regulatory framework, enhancing inter-agency collaboration, and increasing public awareness are considered essential strategies for reinforcing consumer legal protection. This study contributes to the development of legal and regulatory discourse on consumer protection and provides strategic recommendations for improving the governance of cosmetic product supervision in Indonesia.